Benefits of Urban Parks in Different Land Uses - Wei-Ting Chen; Sheng-Jung Ou (Engineering Proceedings, 2025)
With continuous urbanization, cities are facing numerous challenges. In addition, the construction and effective management of urban green spaces have become essential for the sustainable development of healthy cities. In previous studies, algorithms were developed to select appropriate locations for parks with distinctive green patches. Although the suitability of urban parks has been discussed from various perspectives, the location and land use around parks have been rarely considered. Therefore, the benefits and importance of parks across various land uses were assessed in this study. Based on the assessment results, improvement strategies for future park planning and development were proposed. By highlighting and integrating the benefits of different parks, urban green spaces can be expanded to deliver diverse benefits and contribute to healthy and sustainable development. We compiled 35 items in four major types of park benefits from a literature review. Using the Delphi method, 24 important benefits of parks were identified. An importance–performance analysis (IPA) was then conducted to create matrix diagrams for parks in different land use zones to understand the key benefits and identify areas that require priority improvement. The IPA results indicated that parks in residential and industrial areas need to improve ecological benefits and environmental functions for sustainable development. Parks in districts have greening and visual appeal but need improvement in environmental education. There are excessive facilities for passive activities in parks, suggesting a need for resource optimization. The results of this study help urban planners find region-specific design solutions for different land uses and effectively manage and optimize resource allocation.